Kepemimpinan Visioner Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SMP Islam Ar-Rochmah - Putri, Rizky Ananda; Ramadhan, Ganang; Fauzi, Anis; Zohriah, Anis (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to identify and analyze the visionary role of the principal at Ar-Rochmah Islamic Middle School and the strategies implemented in improving the quality of education. Specifically, this research has two main focuses: (1) revealing the role of the principal's visionary leadership in the educational context at Ar-Rochmah Islamic Middle School, and (2) evaluating the strategies used by the principal to improve the quality of education. This research applies a case study approach in qualitative methods. Data was obtained through in-depth interactions through interviews, participation in observations, and careful document analysis. Research findings indicate that school principals play a significant role in formulating and conveying a holistic educational vision, integrating Islamic values ​​in the curriculum, and creating a supportive learning atmosphere. The strategies implemented include developing a character-based curriculum, increasing teacher capacity through training programs and workshops, and regular supervision of the teaching and learning process. Apart from that, the school principal builds harmonious relationships between teachers and students and encourages regular religious activities. This research provides insight into the importance of visionary leadership in the context of Islamic education and offers practical recommendations for school principals and other educational administrators in efforts to improve the quality of education. Thus, it is hoped that the findings from this research can enrich the theoretical foundation and increase practical implementation in the field of leadership in Islamic-based schools.